A Maternity different: Breastfeeding and Phytotherapy - María Dolores Hernández Benítez; Elsa Graciela Rivera Herrera; Cielito del Rosario Bethancourt Jimbo (Fundación para el Desarrollo de la Enfermería, 2013)
The use of complementary health therapies has grown progressively since the 1950s. This article presents a bibliographical review on galactogogues. The main objective is to identify scientific evidence of plants used traditionally as galactogogues in our environment, and its efficacy and safety. We carried out a literature review in order to find the scientific evidence available on the Cochrane Library databases, CINAHL, MEDLINE, and Cuidatge CUIDEN. The keywords used were: phytotherapy, breastfeeding galactogogues, herbal agents, herbal products, breastfeeding and galactogogues. To conclusion although the use of natural remedies, improve breastfeeding should provide accurate and updated health information and women transmit security capabilities.